2019
DOI: 10.3390/plants8110498
|View full text |Cite
|
Sign up to set email alerts
|

The Development and Characterization of Near-Isogenic and Pyramided Lines Carrying Resistance Genes to Brown Planthopper with the Genetic Background of Japonica Rice (Oryza sativa L.)

Abstract: The brown planthopper (BPH: Nilaparvata lugens Stål.) is a major pest of rice, Oryza sativa, in Asia. Host plant resistance has tremendous potential to reduce the damage caused to rice by the planthopper. However, the effectiveness of resistance genes varies spatially and temporally according to BPH virulence. Understanding patterns in BPH virulence against resistance genes is necessary to efficiently and sustainably deploy resistant rice varieties. To survey BPH virulence patterns, seven near-isogenic lines (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(60 citation statements)
references
References 70 publications
(128 reference statements)
4
24
0
Order By: Relevance
“…In our study, NIL-BPH17 showed strong resistance (ambient: 2.4; 2050: 2.3; and 2100: 1.3) in the SSST experiment. These results were consistent with another NIL-BPH17 study under the ambient temperature condition (Nguyen et al 2019). In addition, the NIL-BPH17 gene exhibited a strong inhibitory effect on several N. lugens parameters, such as in the honeydew assay, PGR, survival rate, fecundity, and choice tests, where our results were consistent with those of (Liu et al 2015).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In our study, NIL-BPH17 showed strong resistance (ambient: 2.4; 2050: 2.3; and 2100: 1.3) in the SSST experiment. These results were consistent with another NIL-BPH17 study under the ambient temperature condition (Nguyen et al 2019). In addition, the NIL-BPH17 gene exhibited a strong inhibitory effect on several N. lugens parameters, such as in the honeydew assay, PGR, survival rate, fecundity, and choice tests, where our results were consistent with those of (Liu et al 2015).…”
Section: Discussionsupporting
confidence: 92%
“…In addition, BPH20 did not inhibit several N. lugens parameters, such as the PGR, survival rate, fecundity, and hatchability. Moreover, it has been reported that NIL-BPH20 and the susceptible donor, Taichung 65, showed similar N. lugens adult mortality with two N. lugens colonies (Nguyen et al 2019). Thus, these results indicate that NIL-BPH20 may contain N. lugens tolerance and weak antixenosis and antibiotic effects.…”
Section: Discussionmentioning
confidence: 88%
“…Detailed studies on the production and actions of defense metabolites across gradients of tolerable temperatures are recommended to further elucidate the mechanisms leading to a lower efficiency of antibiosis defenses against adult planthoppers in rice at elevated temperatures. Currently, a range of near-isogenic rice lines with planthopper resistant genes are available to support further research in this area 17,32 . IR62 has been widely planted in Cambodia and in Mindanao (Philippines); although current rates of adoption are not known 19 .…”
Section: N1 N2 N3mentioning
confidence: 99%
“…Meanwhile, volatiles from Rathu Heenati and PTB33 increase planthopper adult and nymph mortality and decrease adult settling and feeding 30 . Because of the spectrum and durability of varieties with the BPH32 gene, PTB33, Rathu Heenati and related lines have become popular resistance donors in rice breeding programs that target planthopper hotspots 20 , 27 , 29 , 31 , 32 .…”
Section: Introductionmentioning
confidence: 99%
“…We used a susceptible rice variety (TN1) as a control and a moderately resistant rice variety (YHY15) carrying the resistance gene BPH15 [12]. It has been found that resistance genes impair BPH feeding behavior on varieties and cause BPH physiological changes by increasing mortality rates, extending developmental periods, and reducing reproductive output [10,13,14]. BPHs that are allowed to feed on resistant rice for a long time may slowly evolve into new virulent BPH populations to overcome rice resistance [15].…”
Section: Introductionmentioning
confidence: 99%